Investigation of the Characteristic Properties of Lignin-Modified Bitumen - Stavros Kalampokis; Marianna Papamoschou; Danai Maria Kalama; Christina P. Pappa; Evangelos Manthos; Konstantinos S. Triantafyllidis (CivilEng, 2022)
The main objective of this study was to investigate the characteristic properties of lignin-modified bitumen with different lignin contents. The first step was the characterization of the physicochemical and thermal properties of the kraft lignin powder along with the determination of its microstructure. This was achieved by carrying out an elemental analysis, Gel Permeation Chromatography (GPC), Thermogravimetric Analysis (TGA)/Derivative Thermogravimetry (DTG), Fourier Transformation Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), Dynamic Light Scattering (DLS) and Confocal Microscopy. After the latter tests, three (3) blends with different lignin contents (5%, 10% and 15% by weight of bitumen) were produced. Characteristic properties such as penetration, softening point, elastic recovery, force ductility, dynamic viscosity and storage stability were determined for the reference bitumen and the three lignin blends. The main conclusion was that kraft lignin powder hardens the conventional bitumen. Specifically, the addition of 15% lignin to the bitumen hardened the blend to such a degree that the bitumen changed category from 50/70 to 35/50 with respect to EN 12591.